Marketing activities effects on brand awareness generation, image and loyalty in the social networks of a public higher education institution - Miriam Nanyeli Sánchez Garza; Mónica Lorena Sánchez Limón; Yesenia Sánchez Tovar; Sikander Ali Qalati (Cogent Business & Management, 2024)
The objective of this research is to examine the effect of marketing activities on brand awareness generation, image and loyalty in social networks of a public higher education institution, based on the social networks theory and Bilgin's model (2018). The quantitative method is used, with the application of 1600 surveys to university students, whose data is analyzed using the structural equations method. As a result of the analysis, it is concluded that substantial marketing activities in a different business environment for a public higher education institution are made up of four dimensions: entertainment, sharing, advertising and personalization. It is also concluded that these activities have a positive effect on brand awareness and loyalty generation.
Keywords: 650; Social networks; marketing strategies; brand awareness; brand loyalty